Sunnah as a Bridge between Theological and Practical Dimensions - Faris, Salman (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This research delves into the multifaceted role of Sunnah as a vital bridge connecting the theological and practical dimensions of Islam. By examining the theological foundations of Sunnah, exploring its relationship with the Qur'an, and investigating its compilation and preservation, this study elucidates the paramount significance of Sunnah in safeguarding the spiritual legacy of Islam. Employing a comprehensive interdisciplinary approach, this research underscores Sunnah's pivotal role as a source of moral and ethical guidance, investigating its influence on individual character and communal behavior. Methodologically, this study employs qualitative analysis, drawing on classical Islamic texts, scholarly opinions, and historical records to construct a comprehensive narrative. Additionally, contemporary perspectives are integrated to highlight the relevance of Sunnah in the modern context. The legal and juridical implications of Sunnah are examined within Islamic thought and practice, uncovering its profound impact on legal frameworks. Through an exploration of rituals and worship, this research unveils Sunnah's transformative power in establishing profound spiritual connectivity. Furthermore, it illuminates the guiding light that Sunnah provides in social and interpersonal relations, fostering harmonious community interactions. This study establishes Sunnah as a dynamic and indispensable bridge, synthesizing theological foundations with practical application. It underscores the enduring relevance of Sunnah in contemporary times, reinforcing its role as a guiding compass for individuals and societies alike, fostering holistic development and ethical progress.